2001
DOI: 10.1128/jvi.75.3.1205-1210.2001
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Mouse Interleukin-4 by a Recombinant Ectromelia Virus Suppresses Cytolytic Lymphocyte Responses and Overcomes Genetic Resistance to Mousepox

Abstract: Genetic resistance to clinical mousepox (ectromelia virus) varies among inbred laboratory mice and is

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
280
2
6

Year Published

2002
2002
2016
2016

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 502 publications
(293 citation statements)
references
References 46 publications
5
280
2
6
Order By: Relevance
“…Indeed, infection of C57BL͞6 mice with recombinant ECTV encoding IL-4 was shown to enhance virus replication and transformed an inapparent infection to full-blown mousepox (33). This report is consistent with our findings, which has established that the susceptible phenotype of BALB͞c and A͞J mice is associated with a type 2 cytokine response, with little or no IFN-␥.…”
Section: Discussionsupporting
confidence: 92%
“…Indeed, infection of C57BL͞6 mice with recombinant ECTV encoding IL-4 was shown to enhance virus replication and transformed an inapparent infection to full-blown mousepox (33). This report is consistent with our findings, which has established that the susceptible phenotype of BALB͞c and A͞J mice is associated with a type 2 cytokine response, with little or no IFN-␥.…”
Section: Discussionsupporting
confidence: 92%
“…Previous studies reported that IFN-γ production from murine NK cells cultured in the presence of IL-4 was not detected (9). IL-4 exposure also suppressed the cytotoxic capacity of NK cells in both in vitro and in vivo models (10,11). However, in contrast to those findings, IL-4 was suggested to induce IFN-γ production by NK cells.…”
mentioning
confidence: 62%
“…For instance, IL-4 has been shown to be essential for the development of a protective anti-malaria CD8 T cell response (22), whereas other studies show that the CD8-mediated protection against viruses or tumors was impaired by IL-4 (23,24). However, the nature of the genes and underlying effector functions regulated by IL-4 in CD8 T cells remain unknown.…”
mentioning
confidence: 99%